Extraction, Purification, Structural Characteristics, Biological Activities, and Applications of Polysaccharides from Gastrodia elata: A Review - Yan Yang; Yonglin Hai; Yongcheng Yang; Rouyuan Wen; Le Wang; Yan Qian; Jiaxian Zhang; Yongguo Li; Zhilong Shi; Haizhu Zhang (Molecules)
Gastrodia elata Blume is a well-known medicinal and edible plant in China, celebrated for its extensive history in traditional medicine and functional food applications. Among its key bioactive components, polysaccharides have drawn significant attention from researchers in the fields of health food and medicine due to their potential health benefits. Recent studies have revealed various biological activities associated with G. elata polysaccharides, including antioxidant, anti-tumor, anti-inflammatory, antibacterial, anti-aging, immune regulation, and neuroprotective properties. However, a comprehensive overview of these polysaccharides remains elusive. Specifically, relationship between the structure and activity of G. elata polysaccharides, along with the mechanisms through which various types exert their biological effects, has yet to be fully elucidated. This knowledge gap may impede the further development and utilization of G. elata polysaccharides in medicine, health products, food, and cosmetics. This paper provides a comprehensive overview of recent advancements in extraction, separation, purification, biological activities, and applications of G. elata polysaccharides. Additionally, it delves into structure-activity relationships and pharmacological mechanisms of these polysaccharides, giving support for future research to enhance their application in medicine, food, health products, and cosmetics.